Rethinking mixed race - Parker, David, 1967 January 22-; Song, Miri, 1964- (London ; Sterling, Va. : Pluto Press, 2001)
Explores the complexities of mixed race in Britain and the USA.
Introduction: Rethinking 'Mixed Race' / David Parker and Miri Song -- How Sociology Imagined 'Mixed Race' / Frank Furedi -- Re-Membering 'Race': On Gender, 'Mixed Race' and Family in the English-African Diaspora / Jayne O. Ifekwunigwe -- Same Difference: Towards a More Unified Discourse in 'Mixed Race' Theory / Minelle Mahtani and April Moreno -- The Subject is Mixed Race: The Boom in Biracial Biography / Paul Spickard -- Triples - The Social Evolution of a Multiracial Panethnicity: An Asian American Perspective / Laurie M. Mengel -- Colour, Culture and Class: Interrogating Interracial Marriage and People of Mixed Racial Descent in the USA / Stephen Small -- 'Mixed Race' in Official Statistics / Charlie Owen -- Learning to Do Ethnic Identity: The Transracial/Transethnic Adoptive Family As Site And Context / Barbara Ballis Lal -- 'I'm a Blonde-haired, Blue-eyed Black Girl': Mapping Mobile Paradoxical Spaces among Multiethnic Women in Toronto, Canada / Minelle Mahtani.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Multiracial people; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; SOCIAL SCIENCE -- Ethnic Studies -- General; Multiracial people; Interethnische Herkunft; Aufsatzsammlung; Groḃritannien; USA; Aufsatzsammlung